Say on pay effectiveness, corporate governance mechanisms, and CEO compensation alignment - Gregorio Sánchez Marín; Gabriel Lozano-Reina; J. Samuel Baixauli-Soler; Maria Encarnacion Lucas-Perez (BRQ Business Research Quarterly, 2017)
Say on pay (SOP) is a relatively new governance mechanism that allows shareholders to pronounce on the suitability on executives' compensation. The literature has mainly examined SOP effects on Anglo Saxon contexts of corporate governance, reporting mixed results and highlighting the need to deepen our understanding of its real impact, as well as its interactions with other mechanisms of governance. Concerning these gaps, the present research analyzes the effectiveness of SOP as a mechanism for aligning CEO compensation in the context of Spanish listed companies – a good representative model of continental European systems of corporate governance–. It also examines the moderating effect of board monitoring and ownership structure. Using panel data and linear regression methodologies on a set of companies from 2013 to 2016, the results show that SOP generally increases the alignment of CEO compensation, although its effectiveness is reduced in companies with overcompensated CEOs and in owner-managed companies."
Keywords: 650; CEO compensation; Say on pay; Corporate governance; Board monitoring; Ownership structure